To simplify the expression 3+4j÷-3-j, we can rewrite it as follows:
3 + 4j ÷ (-3 - j)
To divide complex numbers, we multiply the numerator and denominator by the conjugate of the denominator:
= (3 + 4j) × (-3 + j) ÷ ((-3 - j) × (-3 + j))
Using the distributive property, we can multiply the numerators:
= (-9 - 3j + 12j - 4j^2) ÷ (-3^2 - j^2)
Since j^2 is equal to -1, the expression simplifies to:
= (-9 + 9j) ÷ (9 + 1)
= (-9 + 9j) ÷ 10
= -0.9 + 0.9j
Therefore, 3 + 4j ÷ -3 - j simplifies to -0.9 + 0.9j.
3+4j÷-3-j
1 answer